Building Integrated Photovoltaics for Energy Load Reduction and Supply - Hawiwo, Mohamed (Libyan Journal for Engineering Research, 2017)
Photovoltaics as an environmentally friendly source of energy are still considered as an economically expensive method of electricity production. However, replacing the conventional elements of the building envelope (façade, shading devices, skylights, etc.) with PV modules, the total cost of a built construction is remarkably reduced. The main aims of this study to use building integrated photovoltaic (BIPV) system beside its functions that has mentioned above, to reduce the energy consumption from the cooling load of buildings in warm climate regions. The paper investigated the optimum integration of the photovoltaic system into the building envelope that could produce a reasonable power output and minimizes the heat gains in warm climate regions. The simulation software Autodesk Ecotect Analysis was used to simulate three main PV integrations, window sunshade, roof screen and double skin façade into an assumed office-building model located in the city of Benghazi, Libya. The simulations provided good information for analyzing the potential contribution of the BIPV system on the energy saving according to the PV thermal performance and the power supply generated from the sun, and the final discussion results in choosing the sunshade PV integration as the optimum integration that could produce a reasonable power output and minimizes the heat gains in warm climate regions.